NILAI KEARIFAN LOKAL DALAM E-BOOK LEGENDA DI NATUNA KARYA DINAS PARIWISATA KABUPATEN NATUNA - Hardianti; Suhardi; Patria, Robby; Andheska, Harry; Malik, Abdul; Zaitun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the local wisdom found in the e-book Legenda di Natuna published by the Natuna Regency Tourism Office. The data sources consist of seven regional legends, namely Legenda Tanjung Senubing, Legenda Batu Kasah, Legenda Pulau Senua, Legenda Telapak Kaki Tok Nyong, Legenda Teluk Panglima, Legenda Pulau Sahi, and Legenda Tok Ibo dan Tok Umbok. This research employs a qualitative approach using a descriptive method. The data, in the form of words, phrases, and sentences containing elements of local wisdom, were collected through reading and note-taking techniques, and then analyzed through data reduction, data presentation, and conclusion drawing. The results show that these legends reflect the worldview of the Natuna community related to social and cultural life. Local wisdom is manifested through the attitudes and behaviors of the characters in maintaining social harmony, fulfilling life responsibilities, and preserving cultural continuity. Overall, the legends illustrate a balance between harmonious social life and efforts to sustain the local cultural heritage of the Natuna community. Keywords: local wisdom, legend, folklore